2021
DOI: 10.1109/jrfid.2020.3039878
|View full text |Cite
|
Sign up to set email alerts
|

Waveform Optimization Using RF Pulse Signal on Voltage-Doubler Broadband Rectenna

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Apparently, the efficiencies of the modulated waves were lower than that of the CW wave, which is explained by the fact that the peak-to-average power ratios (PAPRs) of the CW and modulated waves were the same. Experimental research has found that the modulated waves with high PAPR would obtain high efficiency when the input power was low [10,11]. Pham et al measured the maximum efficiencies of 74.7% for pulse wave (PW) and 8.3% for CW when the input power was −15 dBm and the load resistance was 100 kΩ [10].…”
Section: Theoretical Analysis Of the Pw Rectifiermentioning
confidence: 99%
See 2 more Smart Citations
“…Apparently, the efficiencies of the modulated waves were lower than that of the CW wave, which is explained by the fact that the peak-to-average power ratios (PAPRs) of the CW and modulated waves were the same. Experimental research has found that the modulated waves with high PAPR would obtain high efficiency when the input power was low [10,11]. Pham et al measured the maximum efficiencies of 74.7% for pulse wave (PW) and 8.3% for CW when the input power was −15 dBm and the load resistance was 100 kΩ [10].…”
Section: Theoretical Analysis Of the Pw Rectifiermentioning
confidence: 99%
“…Experimental research has found that the modulated waves with high PAPR would obtain high efficiency when the input power was low [10,11]. Pham et al measured the maximum efficiencies of 74.7% for pulse wave (PW) and 8.3% for CW when the input power was −15 dBm and the load resistance was 100 kΩ [10]. In [11], the measured results showed that the OFDM, white noise and chaotic signals had a higher efficiency than CW at the input power of −10 dBm.…”
Section: Theoretical Analysis Of the Pw Rectifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Facing the necessity to satisfy the energy needs of smart circuits and sensors, the improvement of DC voltage and/or RF-to-DC conversion efficiency of rectifying circuits and more generally rectennas is presented as a key challenge in particular for low power levels. In order to rise it, and instead of focusing on the rectenna cell, one can take benefit from the transmission strategy by changing the excitation signal [1][2]. In [3][4], the authors present the impact of different waveforms on a series diode converter circuit using signals such as chaotic signal, white noise as well as OFDM and show that waveforms with high Peak to Average Power Ratio (PAPR) increase the RFto-DC conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], multisine signal is used to improve the range and readability of RFID tags. In [6][7], RF pulse signal allows to improve the output DC voltage and efficiency of rectifiers operating at 2.4 GHz when the duty cycle and the load resistances vary. In [8], the authors demonstrate that with the 3-tone Tx waveforms, the IM3 carrier generated by the nonlinear tag can be enhanced by 4 dB.…”
Section: Introductionmentioning
confidence: 99%